The structure of ICD-11 PTSD and complex PTSD in Lithuanian mental health services. Issue 1 (1st January 2018) - Kazlauskas, Evaldas; Gegieckaite, Goda; Hyland, Philip; Zelviene, Paulina; Cloitre, Marylene
ABSTRACT: Background : The updated 11 th edition of International Classification of Diseases (ICD-11) is expected to be released by the WHO in 2018. Disorders specifically associated with stress will be included in a separate chapter in ICD-11, and will include a revision of ICD-10 PTSD as well as a new diagnosis of complex posttraumatic stress disorder (CPTSD). The proposed symptom structures of ICD-11 PTSD and CPTSD have been validated in several studies previously, however few studies have used the International Trauma Questionnaire (ITQ), a specific measure for ICD-11 PTSD and CPTSD. Given that ICD-11 PTSD and CPTSD diagnoses are intended to be applicable across different cultures and nations, it is important that the constructs be evaluated across diverse populations and languages. Objective : Study of the psychological impact of trauma is relatively new in Lithuania, coinciding with its independence from the Soviet Union in the 1990s. Studies thus far reveal a population suffering from the effects of long-term and systematic political oppression and violence. The aim of this study was to assess the validity of the symptoms and structure of PTSD and CPTSD in a Lithuanian treatment-seeking sample as measured by the ITQ. Method : A total of 280 patients from outpatient mental health centres participated in this study. PTSD and CPTSD symptoms were measured with the ITQ. We applied confirmatory factor analysis (CFA) and latent class analysis (LCA) for analysis of data. Results and conclusions : Our study supported the ICD-11 factor structure of CPTSD, and a three-class model was supported in LCA analysis with a PTSD class, a CPTSD class, and a low symptom class. Findings support the factorial and discriminant validity of the ICD-11 proposals for PTSD and CPTSD in a unique clinical population.